Continuous research monitoring improves the quality of research conduct and compliance among research trainees: internal evaluation of a monitoring programme - Akello, Mirriam; Coutinho, Sarah; N-Mboowa, Mary Gorrethy; Bukirwa, Victoria D; Natukunda, Agnes; Lubyayi, Lawrence; Nabakooza, Grace; Cose, Stephen; Elliott, Alison M. (AAS Open Research, 2020)
Background: Research site monitoring (RSM) is an effective way to ensure compliance with Good Clinical Practice (GCP). However, RSM is not offered to trainees (investigators) at African Institutions routinely. The Makerere University/Uganda Virus Research Institute Centre of Excellence in Infection and Immunity Research and Training (MUIIPlus) introduced internal monitoring to promote the quality of trainees’ research projects. Here, we share our monitoring model, experiences and achievements, and challenges encountered. Methods: We analysed investigators’ project reports from monitoring visits undertaken from April 2017 to December 2019. Monitors followed a standard checklist to review investigator site files and record forms, and toured site facilities. We planned four monitoring visits for each trainee: one at site initiation, two interim, and a closeout monitoring visit. A team of two monitors conducted the visits. Results: We monitored 25 out of the 26 research projects in progress between April 2017 and December 2019. Compliance with protocols, standard operating procedures, GCP, and GCLP improved with each monitoring visit and all projects achieved 100% compliance at site closeout. All investigators had good work ethics and practice, and appropriate facilities. Initially, some investigators’ files lacked essential documents, and informed consent processes needed to be improved. We realized that non-compliant investigators had not received prior training in GCP/GCLP, so we offered them this training. Conclusions: Routine monitoring helps identify non-compliance early and improves the quality of research. We recommend continuous internal monitoring for all research studies. Investigators conducting research involving human subjects should receive GCP/GCLP training before commencing their projects. Institutional higher degrees and research ethics committees should enforce this as a requirement for project approvals.
Keywords: Internal monitoring; Good Clinical Research Practice; Trainees or investigators; Uganda; Africa; Research quality